Pengaruh Waktu Radiasi Gelombang Mikro Terhadap Karakteristik Pori Karbon Aktif Kulit Singkong (Manihot esculenta Crantz) - Rahmawati; Fajri, Rahmatul; Fadlly, T. Andi; Sari, Nirmala; Annisa, Fera; Husna, Siti Sarah (JST (Jurnal Sains dan Teknologi), 2025)
Cassava peel waste is a biomass that has not been optimally utilized, even though it has the potential as a raw material for activated carbon. The problems that arise are the low added value of this waste and the need for efficient technology to produce highly porous activated carbon. This study aims to analyze the effect of variations in microwave irradiation time on the pore characteristics of cassava peel-based activated carbon. This study uses a quantitative approach with a laboratory experimental design. The research subjects were activated carbon resulting from chemical and microwave activation treatments, with three trial groups, each consisting of one activated carbon sample processed for 10, 15, and 20 minutes. Data collection methods were carried out through characterization using X-ray Fluorescence (XRF), Scanning Electron Microscopy (SEM), and Ultraviolet-Visible (UV-Vis) spectroscopy instruments. Data were analyzed descriptively and comparatively to observe pore structure development, elemental composition, and optical properties between samples. The results showed that the longer the microwave activation time, the more the porosity and surface structure of the activated carbon developed, with sample AC20 showing the best pore morphology and the highest absorption value. The conclusion of this study indicates that a combination of chemical and microwave-based activation is effective in producing highly porous activated carbon from cassava peels. This research implies that cassava peel waste can be an alternative solution in developing environmentally friendly adsorbent materials for pollutant remediation applications in aquatic environments.